Integrating Local Wisdom, Sustainability, and Digital Transformation to Empower Msmes in Medan City - Mardelia Desfrida; Abdul Rahman; Rizki Syahputra; Aswin Fahmi D (INFOKUM, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in regional economic development; however, many face challenges in integrating local cultural identity, sustainability, and digital transformation into their business practices. This study develops FoSSEI LOKALITA, an MSME empowerment model that integrates local wisdom, sustainability, digital transformation, and multi-actor collaboration to enhance MSME resilience and competitiveness in Medan City, Indonesia. The study adopts an applied participatory approach by combining Design-Based Research (DBR) and Research and Development (R&D) methods. Data were collected through literature review, observation, interviews, focus group discussions, questionnaires, and expert validation. The findings indicate that although 80% of MSMEs incorporate local cultural elements into their products, 60% have not consistently communicated their cultural identity, 65% lack systematic financial records, and only 18% utilize digital marketplaces. In response, FoSSEI LOKALITAproposes a four-stage empowerment framework comprising local potential identification, capacity building, digitalization and product innovation, and pentahelix-based collaboration and replication. The model positions local wisdom as a strategic source of innovation, sustainability as a governance principle, and digital transformation as a catalyst for market adaptation. This study contributes by introducing an integrated empowerment framework that connects enterprise capacity development with collaborative ecosystem strengthening. The proposed model provides practical guidance for policymakers and development agencies in promoting sustainable, culturally rooted, and digitally enabled MSME development, while offering a foundation for future empirical validation.